The application of periodisation models for athletes of different standards - A practical approach - Abbott, C. (2003)
As the athlete passes through physical and performance maturity, the stimulus required to raise their level of special strength, specialised fitness and specific preparedness for sport drastically changes and so does the method of program prescription. Misapplication of periodisation models will produce sub-standard results, impair the athlete`s ability to perform to the highest potential and may be the cause of injuries or illness. It seems that instead of debating which periodisation scheme is the best, the question should be - which model of planning and organization is most suitable for my athlete? A beginner in almost all instances can get away with a basic program emphasizing progressive overload from session to session, as well as a concurrent training plan devoting time to multiple motor abilities. As the athlete passes to the advanced stage, the ability to emphasize multiple motor qualities at the same time will diminish. To overcome this, a few specific types of training session should be emphasized, with the goal being to improve from week to week. The remaining qualities are maintained with light retaining loads. It has been shown that the conjugate sequence system produces the best results for advanced athletes. This is likely because of the amount of work devoted towards a specific goal is very high, and there are no extraneous stressors to add extra fatigue to the system. This creates a very strong stimulus to adapt over a long period of time. Bompa (1999) also concludes that the approach to periodisation should be in the context of the athletes` readiness for heavy schedule competition irrespective of whether the athlete is in a sport typified by multi-peaks. For novice athletes, he recommends a mono-cycle periodised plan, containing a long preparatory phase free from the stress of competition, allowing the coach to concentrate on developing skills and a strong foundation of physical training. A bi-cycle is suggested for intermediate athletes who can qualify for national championships. Even in this case he suggests a preparatory phase for as long as possible. Finally for advanced, international class athletes a tri-cycle is advocated where it is presumed that they have a solid foundation. Bompa does not specify loading objectives for the training of specific physical traits, but it still supports the assumption that novice athletes can obtain results from a simplistic approach to the planning of their training, such as the Linear model which is mono-cyclic, as it only has one peak and can accommodate a long preparatory phase. Bompa`s view, although technically different from other experts, still supports the contention that the elite class athlete requires more time spent in training geared toward specific physical preparedness for sports, whereas the beginner and intermediate athletes` training must be rooted in longer phases of general preparation and skill acquisition. It is apparent that many experts with differing views mostly still agree on the appropriateness of classifying athletes according to their level of proficiency before applying a periodised model for training The information presented provides us with a choice of answers depending on the level of athlete we are training and the type of sport we are involved in. The list of periodisation models outlined here is not exhaustive by any means, but it presents the theories and thoughts of some of the most influential and successful coaches and scientists involved in physical preparation for sport. As strength and conditioning coaches it is our responsibility to adapt the findings of such experts to our coaching situation and environment. Many of us who may work part-time as coaches may not have the time or resources to prepare and apply such detailed models for our athletes. However, having an awareness of the principles that lie behind the utilisation of periodisation models should allow us to develop a more informed approach and obtain better results. I have learnt that an over-reliance on anything often leads to closed-mindedness. The late Dr. Mel Siff states that the organization of training is as much art, trial-and-error and intuition as it is science, so that periodisation schemes should serve as approximate guidelines to be followed and modified by ongoing analysis of physiological and psychological markers of progress (Siff 2003). Periodisation and the planning of training is an immense topic with many intricacies, the magnitude of which cannot be explored in this article. Unfortunately texts and papers on this topic are mostly either too simplified or grossly over-scientific, meaning that the practicing coach is unable to avail him/herself of understandable knowledge to correctly apply the theories to their athletes. As a result many take the ad-hoc approach where guesswork replaces intuition. It is a given that every strength coach should use periodisation to plan training, but now it should be a given that every coach understands the interaction between the principles of training, basic physiology, the synergistic and interference-causing relationship between training methods and means and the nature of the chosen sport in order to properly plan.